Neutrophils promote the activation of monocytes via ROS to boost systemic antitumor immunity after cryo-thermal therapy - Wang, Shicheng; Zhang, Zelu; Wang, Junjun; Lou, Yue; Zhu, Yongxin; You, Jiaqi; Liu, Ping; Xu, Lisa X. (Frontiers in Immunology, 2024)
The characteristics of the tumor immunosuppressive microenvironment represent a major challenge that limits the efficacy of immunotherapy. Our previous results suggested that cryo-thermal therapy, a tumor ablation system developed in our laboratory, promotes macrophage M1-type polarization and the complete maturation of DCs to remodel the immunosuppressive environment. However, the cells that respond promptly to CTT have not yet been identified. CTT can cause extensive cell death and the release of danger-associated molecular patterns and antigens. Neutrophils are the first white blood cells recruited to sites of damage and acute inflammation. Therefore, we hypothesized that neutrophils are the initial cells that respond to CTT and are involved in the subsequent establishment of antitumor immunity. In this study, we examined the kinetics of neutrophil recruitment after CTT via flow cytometry and immunofluorescence staining and explored the effect of neutrophils on the establishment of systemic antitumor immunity by in vivo neutrophil depletion and in vitro co-culture assays. We found that CTT led to a rapid and strong proinflammatory neutrophil response, which was essential for the long-term survival of mice. CTT-induced neutrophils promoted the activation of monocytes via reactive oxygen species and further upregulated the expression of IFN-γ and cytotoxic molecules in T and NK cells. Adoptive neutrophil transfer further enhanced the antitumor efficacy of CTT in tumor models of spontaneous and experimental metastasis. These results reveal the important role of neutrophil‒monocyte interactions in the development of anti-tumor immunity and highlight that CTT could be used as an immunotherapy for targeting neutrophils and monocytes to enhance antitumor immunity.